Dimensions of Poverty in Kazakhstan, Volume 2. Profile of Living Standards in Kazakhstan in 2002 - World Bank (Washington, DC, 2013)
This report assesses the living conditions in Kazakhstan during 2001-2002, especially as concerning the poor. Based upon consultations with the Government, research institutes, and nongovernmental organizations, three key questions related to poverty were identified as critical to understanding the current situation, and to developing a poverty reduction strategy. These questions are: a) what is the current poverty situation in Kazakhstan, b) what has been the impact of economic growth on poverty, and, c) how effective is the social protection system in alleviating poverty. Six main findings on poverty in Kazakhstan are worth highlighting: 1) Housing poverty and the broader problem of poor quality of basic infrastructure services are prevalent. 2) Rural poverty in particular did not appear to benefit significantly from growth, since it decreased only marginally in these high growth years. 3) The greatest source of inequality in Kazakhstan is the divergence of living conditions across oblasts-whether measured using indicators of consumption expenditures, incomes, usage of services, or health indicators. 4) Though the quality of education cannot be judged from the Household Budget Survey, the productivity of the future labor force could be in jeopardy since an estimated 50 percent of young adults-25-29 year olds-have a secondary school, or lower degree. 5) Infant mortality rates are high. 6) The best program for transferring income to the poor is the Targeted Social Assistance Program, though it requires strengthening of its coverage, and benefit levels.